Picture this as a cooperative learning strategy to develop english foreign language basic writing skills amongst first year of bachillerato students at Pio Jaramillo Alvarado high school. 2014 – 2015 academic period - Yaguachi Cueva, Yesenia Isabel (2016)
The present research was focused on the use of Picture This as a cooperative learning strategy to develop English Foreign Language basic writing skills amongst first year of bachillerato students. An intervention plan consisting of twenty-two lesson plans was carried out to improve the skill, and tests and questionnaires were used to measure students’ progress on writing as well as their behaviors and attitudes toward the strategy mentioned before. The scientific, descriptive, analytic-synthetic and statistical methods were used to describe data, analyze the results and finally, draw conclusions. The results of the posttest and post questionnaires demonstrate an improvement in students writing. Based on the results it might be concluded that the intervention was important because it showed an evident advance in the student’s achievement attributed to the implementation of cooperative learning activities.